Prevalence and risk factors for cervical squamous intraepithelial lesions among women infected with HIV-1 in Makurdi, Nigeria - Swende LT; Ngwan SD; Swende TZ (Dove Medical Press, 2012)
Terrumun Z Swende1,2, Stephen D Ngwan2, Laadi T Swende31Department of Obstetrics and Gynecology, College of Health Sciences, Benue State University, Makurdi, 2Department of Obstetrics and Gynecology, 3Department of Family Medicine, Federal Medical Center Makurdi, Makurdi, NigeriaBackground: The purpose of this study was to determine the prevalence and risk factors for cervical squamous intraepithelial lesions (SIL) among women infected with human immunodeficiency virus type 1 (HIV-1) receiving care at the Federal Medical Center Makurdi, Nigeria.Methods: Between March and December 2009, a total of 253 women infected with HIV-1 had cervical smears taken for cytology. HIV-1 RNA viral load and CD4 counts were also measured.Results: Of the 253 women, cervical SIL were present in 45 (17.8%). However, abnormal cervical cytology was noted in 146 (57.7%). Of those with abnormal cervical cytology, 101 (39.9%) women had atypical squamous cells of undetermined significance, 16 (6.3%) had low-grade SIL, and 29 (11.5%) women had high-grade SIL. The median CD4 lymphocyte count was lower in participants with cervical SIL compared with those without (132 versus 184 cells/mm3; P = 0.03). The median HIV-1 RNA viral load was higher in women with cervical SIL (102,705 versus 64,391 copies/mL; P = 0.02). A CD4 lymphocyte count of <200 cells/mm3 and an HIV-1 RNA viral load of <10,000 copies/mL were found to be significantly associated with cervical SIL.Conclusion: A high prevalence of cervical SIL was found among HIV-1-infected women in Makurdi, Nigeria. Increased immune suppression and HIV-1 viremia are significantly associated with cervical SIL.Keywords: cervical squamous intraepithelial lesions, human immunodeficiency virus, risk factors, immunosuppression, cervical dysplasia, Nigeria